KEPENTINGAN KEBIJAKAN PEMBUATAN PERATURAN DAERAH PROVINSI DAERAH KHUSUS IBUKOTA (DKI) JAKARTA NO. 4 TAHUN 2007 (PENGENDALIAN, PEMELIHARAAN DAN PEREDARAN UNGGAS) DAN IMPLIKASINYA TERHADAP USAHA PENDISTRIBUSIAN UNGGAS DI DKI JAKARTA - Siti Mariam (Institut Ilmu Sosial dan Manajemen STIAMI, 2016)
This research was conducted to find out the following matters: (1) the juridical, philosophy, and sociology aspects of DKI Jakarta Province regulation on poultry distribution, (2) observing and analyzing the poultry relocation and distribution in DKI Jakarta Province, (3) analyzing the implication of local regulation number 4 year 2007 in poultry business.This research was conducted based on local regulation number 4 year 2007 which was supported by legal documents from competence resources in poultry business. The data collected was supported by library research, scientific literatures, books, scientific magazines/journals, statistic data, scientific articles, and reports, and interview to the poultry businessmen. The data was analyzed by using qualitative and quantitative methods due to the type of this research as descriptive study and was legal normative research study.The discussion came to the finding that the importance of composing local regulation policy in DKI Jakarta Province number 4 year 2007 was to prevent the disseminating and the spreading of avian influenza in order to protect the community and to provide economic opportunity for local government or private sectors to manage the chicken accommodating location (TpnA) and the chicken butchering location (TPA) in order to get income. By deciding the TpnA and TPA in five location, it caused the accommodation and the butchering industries more concentrated and decrease the competition intensity in poultry business. PT Kartika Eka Dharma in west Jakarta and PT Dharma Jaya as well as PD Dharma Jaya that were appointed as chicken butchering location and chicken accommodating location operators became the form of government discrimination toward the poultry businessmen.